Multidisciplinary approach in parenteral antibiotic therapy - Ćetković, Zora; Rajinac, Dragana (Archives of Pharmacy, 2022)
Unsafe medication use and medication errors are a leading problem in healthcare systems around the world. Since parenteral antibiotics have a higher risk of side effects, higher costs associated with medication administration by the parenteral route and require well trained hospital staff, it is necessary that doctors and nurses/technicians collaborate together with hospital pharmacists. The aim of the study was to determine whether there is a need for multidisciplinary approach in parenteral antibiotic therapy in different hospital settings.The study was conducted as a cross-sectional study in twelve hospitals in Serbia, Croatia, Slovenia, Bosnia and Herzegovina, North Macedonia and Montenegro, from May to September 2021. The study was conducted by hospital pharmacists and included doctors and nurses/technicians. A previously validated questionnaire regarding the use of parenteral antibiotics and a socio-demographic questionnaire were used as a research instument. The research included 565 healthcare professionals, 206 doctors and 359 nurses/technicians. The results demonstrated the need for collaboration between doctors, nurses/technicians and hospital pharmacists in parenteral antibiotic therapy, since most doctors stated that they rely on the advice of pharmacists when it comes to the stability of reconstituted antibiotics, incompatibility with other medicines and method of administration, volume of solvents and/or duration of infusion when prescribing parenteral antibiotics for special patient groups. This study highlights the importance of a multidisciplinary approach in making the right decisions regarding antibiotic choice, dose, route of administration and duration of therapy, in order to achieve satisfactory clinical and economic outcomes.